The effect of career calling on medicine students’ learning engagement: chain mediation roles of career decision self-efficacy and career adaptability - Jingyuan Chen; Jingyuan Chen; Hongfeng Liu; Jinku Wang (Frontiers in Medicine)
The study investigates the influence of career calling on the learning engagement of medical students in higher vocational colleges, focusing on the chain mediation roles of career decision self-efficacy (CDSE) and career adaptability. A cross-sectional survey was conducted with 173 students from three vocational colleges across China, utilizing various scales to measure career calling, learning engagement, career adaptability, and CDSE, and structural equation modeling was employed to analyze the survey data. Chain mediation analysis revealed a significant positive correlation between career calling and learning engagement among medical students. Career adaptability was found to partially mediate the relationship between career calling and learning engagement, while CDSE did not exhibit a significant mediating effect. However, when both career adaptability and CDSE were considered as chained mediators, they had a significant indirect effect on the relationship between career calling and learning. The findings highlight the pivotal significance of cultivating a strong career calling and augmenting career adaptability as strategic approaches to bolster learning engagement among medical students in higher vocational colleges.